2014
DOI: 10.22459/her.20.02.2014.06
|View full text |Cite
|
Sign up to set email alerts
|

Place Matters: An Investigation of Farmers’ Attachment to Their Land

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 26 publications
1
16
0
2
Order By: Relevance
“…Hence, in the present analysis we considered values to be fundamental permeating motives that are closely related to situations and specific circumstances. A farmer may moreover be motivated by a range of factors, from financial to more social and emotional (Burton ; Quinn and Halfacre ; Howley et al . ).…”
Section: Farmers' Values and Decision Makingmentioning
confidence: 99%
“…Hence, in the present analysis we considered values to be fundamental permeating motives that are closely related to situations and specific circumstances. A farmer may moreover be motivated by a range of factors, from financial to more social and emotional (Burton ; Quinn and Halfacre ; Howley et al . ).…”
Section: Farmers' Values and Decision Makingmentioning
confidence: 99%
“…While we did not investigate personal reasons behind feelings of professional efficacy, it has been reported that farmers find meaning and value in their roles as stewards of the land and caretakers of animals [33]. This view of farming as "a calling that provides purpose to their lives" [33] (p. 127) may also help explain our professional efficacy findings. Personal accomplishment/professional efficacy is positively associated with control coping [28], "suggesting that a problem-focused response and a positive self-appraisal may be mutually reinforcing" (p. 130).…”
Section: Professional Efficacymentioning
confidence: 86%
“…Indeed, personal accomplishment (a subscale on the MBI-HSS that is analogous to professional efficacy and that "assesses feelings of competence and successful achievement in one's work with people") [20] (p. 15) is reportedly associated with work friends, participation, and team orientation [28]. While we did not investigate personal reasons behind feelings of professional efficacy, it has been reported that farmers find meaning and value in their roles as stewards of the land and caretakers of animals [33]. This view of farming as "a calling that provides purpose to their lives" [33] (p. 127) may also help explain our professional efficacy findings.…”
Section: Professional Efficacymentioning
confidence: 95%
“…Efforts to provide context and understand the topics for exploration came first. The reviewed literature ranged from underpinnings of Southern Agrarians and local food traditions in the U.S. South (Grey 2014;Prody and Inabinet 2014;Prody 2013) and articles on the environmental impacts of agriculture and the U.S. Farm Bill (Quinn and Halfacre 2014;Foley et al 2011) to a study in multimedia ethnographic research methodology (Tobin and Hsueh 2007). Students also learned about the culture of the Na and Nuosu villages of southwest China to gain deeper understanding of the audiences that would participate in the media exchange (Blumenfield 2003;Blumenfield 2014).…”
Section: On the Webmentioning
confidence: 99%